2018
DOI: 10.1186/s13012-018-0818-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of collaborative care management for depression in primary care settings with academic affiliations across New York State

Abstract: BackgroundIn a large statewide initiative, New York State implemented collaborative care (CC) from 2012 to 2014 in 32 primary care settings where residents were trained and supported its sustainability through payment reforms implemented in 2015. Twenty-six clinics entered the sustainability phase and six opted out, providing an opportunity to examine factors predicting continued CC participation and fidelity.MethodsWe used descriptive statistics to assess implementation metrics in sustaining vs. opt-out clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 29 publications
(25 reference statements)
0
45
0
1
Order By: Relevance
“…Thus, our results can, at least to a certain extent, be transferred to other countries and regions, especially to care provided without co-location. Although the present study provides insights into collaboration in CSC models, further research is needed as to the sustainability of such models outside of trials, as this has been identified as challenge [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results can, at least to a certain extent, be transferred to other countries and regions, especially to care provided without co-location. Although the present study provides insights into collaboration in CSC models, further research is needed as to the sustainability of such models outside of trials, as this has been identified as challenge [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggests that even with a great deal of TTA geared toward implementing CoCM, NYS CCMP practices still needed post-implementation support to succeed in sustaining it (19). OMH has used the data in clinics' quarterly metrics reports to identify areas for quality improvement and reached out to speci c clinics for targeted, post-implementation TTA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of TTA in ensuring successful implementation and outcomes. In addition, they found most real-world implementations of CoCM actually see outcomes below that of RCTs and those that NYS has achieved (19). Future studies may take a deeper dive into the nuances of TTA such as the impact of different types, i.e., individual coaching calls vs. webinars or group trainings, and could also further de ne intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the PCC managers underlined the benefit of the targeted financial resources from the region for overcoming obstacles, which gave opportunities to replace the nurse who took on the role of care manager. Previous studies have shown that economic incentives are important when implementing collaborative care [21, 23, 26] and for encouraging change and improving long term results [27].…”
Section: Discussionmentioning
confidence: 99%